2016
DOI: 10.21053/ceo.2015.01116
|View full text |Cite
|
Sign up to set email alerts
|

Audiologic Patterns of Otic Capsule Preserving Temporal Bone Fracture: Effects of the Affected Subsites

Abstract: Objectives.This study was aimed to assess the relationship between the type of temporal bone area involved and conductive hearing loss.Methods.We enrolled 97 patients who visited the otolaryngology clinics of Seoul National University Hospital or Boramae Medical Center, Seoul Metropolitan Government-Seoul National University with temporal bone fracture between January 2004 and January 2014. Audiometric parameters, including initial and improved air-bone (AB) conduction gap values, were reviewed in accordance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Kim Correlation between hearing loss and otic capsule sparing fracture with temporal bone sub-sites showed very weak positive correlation (R value 0.2064). Study done by Kim So Young, et al showed CHL that occurred after otic capsule-sparing temporal bone fractures varied in accordance with the temporal bone sub-sites [6].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kim Correlation between hearing loss and otic capsule sparing fracture with temporal bone sub-sites showed very weak positive correlation (R value 0.2064). Study done by Kim So Young, et al showed CHL that occurred after otic capsule-sparing temporal bone fractures varied in accordance with the temporal bone sub-sites [6].…”
Section: Discussionmentioning
confidence: 97%
“…But this classification system fails to predict the severity of conductive hearing loss in otic capsule sparing temporal bone fractures [5]. So Young Kim et al studied various audiometric patterns in otic capsule sparing fractures and proposed a sub-site classification system to predict the severity of the hearing loss [6]. In this study, an attempt is being made to correlate the severity of the hearing loss in otic capsule sparing fracture patients based on the sub-site classification system.…”
Section: Open Accessmentioning
confidence: 96%
“…Conductive hearing loss is due to middle ear injuries, such as hemotympanum and ossicular disruption. Kim, et al [15] reported larger air-bone gaps (AB gaps) in patients with ossicular chain involvement than in those with no ossicular chain involvement, which is caused by hematoma and hemotympanum. Grant, et al [16] reported that AB gaps decreased from 24.8 dB to 13.2 dB on average.…”
Section: Discussionmentioning
confidence: 99%
“…Este síntoma generalmente va acompañado de otorragia y hemotímpano debido al daño de diferentes estructuras internas del oído. Diferentes estudios han demostrado la relación entre el tipo de fractura de hueso temporal y el tipo de pérdida auditiva encontrando que las fracturas longitudinales están más asociadas al tipo conductivo mientras que las transversales al tipo neurosensorial, afectando la calidad de vida de quien las padece (14)(15)(16)(17)(18)(19)(20). En los casos donde se presenta compromiso de estructuras laberínticas se observa una asociación a vértigo e hipoacusia neurosensorial (3)(4)(5).…”
Section: Discussionunclassified
“…En el oído medio la estructura más frecuentemente afectada es la cadena osicular, siendo de estas más frecuentes las luxaciones (93%) que las fracturas (7%) (4-5). La luxación incudoestapedial es la más frecuente en un 82% de los casos, y la luxación incudomaleolar en el 52%, asociada en la mayoría de los pacientes a fracturas de la apófisis larga del yunque, del cuerpo del estribo o de presentarse concomitantemente con luxaciones incudoestapediales (12)(13)(14)(15).…”
Section: Introductionunclassified